THE IMPACT OF SOCIAL MEDIA AND ARTIFICIAL INTELLIGENCE ON YOUNG PEOPLE’S SPEECH AND THINKING ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article analyzes the impact of social networks and artificial intelligence technologies on the speech and thinking of young people. The changes taking place in the process of acquiring knowledge, thinking skills and speech culture of young people in the modern digital environment are highlighted. Also, the positive and negative aspects of this process are explained based on the views of representatives of Uzbek literature. At the end of the article, conclusions are drawn about the need for balanced use for young people.